Evolution of physical properties in different performance levels in soccer players - Rodriguez-Rosell, D.; Franco-Marquez, F.; Pareja-Blanco, F.; Gonzalez-Badillo, J. J. (17th Annual Congress of the European College of Sport Science (ECSS), Bruges, 4. -7. July 2012, 2012)
During a soccer game, endurance plays an important role on performance. Nevertheless, the most conclusive actions are realized at maximum intensity and short periods of time (2). Several works have analyzed correlations among different variables (1RM half squat, sprint and jumping height) in elite soccer players (3). However, to our knowledge there has been no study to analyze the correlation between strength and endurance variables throughout a soccer player´s life. Methods: One hundred forty-eight male soccer players belonging to the same football club took part in this study. The subjects were divided into seven different teams according to age and category (T1: 11.9±0.2, T2: 12.6±0.5, T3: 13.8±0.5, T4: 14.6±0.5, T5: 16.2±0.5, T6: 17.3±0.6, T7: 24.4±4.5 years). The evaluation was done at the beginning of the season and the variables measured were: countermovement jump (CMJ), full squat 1RM (T-Force System, Ergotech, Spain), acceleration capacity in 10, 20 m (T10, T20, T10-20), maximal aerobic speed (MAS) and maximal throw velocity (MTV). One-way ANOVA was used to detect differences between groups of subjects. The correlation between variables was determined through Pearson`s coefficient correlation taking as the control variable age of subjects. Results: Every variable measured displayed high reliability (CCI: 0.914-0.997; CV: 1.94-2.61%). As a result we obtained that every physical qualities measured (1RM, CMJ, T10, T20, T10-20, MAS and MTV) improved progressively with age, reaching statistically significant differences (p<0.05) between each category in most cases. Furthermore, we found statistically significant correlations (p<0.01) between each performance analyzed variables (0.36-0.95). Discussion: This study indicates that with increasing age of soccer players, those variables that can be explained through improvement of strength (CMJ, 1RM full squat, T10, T20, T10-20 and MTV) show more gains than those variables that depend on endurance (MAS), which do not show improvements after 14 years. These findings could indicate that factors which explain soccer performance would be more related with explosive-type actions (changes of direction, jumps, sprints, tackles) (1) where a high production of strength, power and rate of force development have a more determinant role than MAS.